Teachers Readiness In The Process Of Implementing The Independent Learning Curriculum In Elementary School - Nurul Alga Fitri; Faizal Chan; Issaura Sherly Pamela (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
This study aims to determine the readiness of teachers in implementing the Independent Curriculum in elementary schools. This research was conducted at the State Elementary School 34/I Teratai, Kec. Muara Bulian Kab, Batang Hari, Jambi Province. The type of research used is qualitative research with descriptive research. The research data were obtained through observation and interviews (as the main data) and document studies (as supporting data). The results in this study indicate that teacher readiness is an important component in curriculum implementation. teacher readiness in the process of implementing the independent curriculum at SDN 34/I is in the pretty good category. This is related to the teacher's presentation of the independent curriculum which shows that the teacher understands well the concept, objectives, mechanisms and structure of implementing the independent curriculum, but there are still a number of things that need to be studied further regarding lesson planning or making teaching modules. At the implementation stage the teacher has implemented the independent curriculum in accordance with government directives, namely carrying out project learning to strengthen the Pancasila student profile (P5) and differentiated learning. At the assessment stage the teacher carries out diagnostic, formative and summative assessments and processes these assessments to see the achievement of learning and become evaluation material. From the research results obtained, for the process of implementing the independent curriculum in the first year, schools and teachers are expected to always work together so that the process of implementing the independent curriculum is more optimal. It is hoped that the results of this study can have benefits for further research.